Promoting oral and dental healthcare among the elderly in a residential care home in Isfahan: a best practice implementation project. Issue 1 (14th March 2023) - Vedaei, Amirhossein; Iranmanesh, Pedram; Tahani, Bahareh; Mostafaei, Ali; Talebpour, Amin
ABSTRACT: Introduction: Oral health is an important aspect of general health, which affects the wellbeing and quality of life of older adults. Residents in aged care facilities often suffer from overall dental neglect and insufficient oral healthcare, leading to moderate-to-high levels of oral diseases. Furthermore, physical or mental health concerns may result in difficulties in maintaining good oral health. Objectives: This implementation project aims to audit and improve the oral healthcare status of the elderly living in a residential care home in Isfahan, Iran using the JBI evidence summary. Methods: The methods are preimplementation and postimplementation design using audit and feedback with a situational analysis to guide implementation planning. Seven evidence-based quality indicators were used to measure preintervention compliance with the best practice. Situational analysis was used to identify and target barriers through locally developed practice change strategies following which a repeat audit was conducted at 4 months. Four nursing staff, 11 caregivers, and 38 residents were interviewed for both the baseline and the follow-up audit. Results: Compliance rates improved for all seven criteria except the use of a soft-bristled toothbrush (criterion 6). All eight categories of criterion 2 measuring assessment of oral health improved by at least 10%, with the largest improvements in saliva assessment and gingiva assessment. Criterion 1 (oral health training for caregivers) reached the greatest compliance rate (100%). Conclusion: The implemented strategies included improving knowledge and changing the attitudes of the caregivers through organizing educational sessions. These strategies were developed to address process and structural barriers to best practice and were helpful for staff uptake of evidence.